Vibrio cholerae RND efflux systems: mediators of stress responses, colonization and pathogenesis - Bina, X. Renee; Bina, James E. (Frontiers in Cellular and Infection Microbiology, 2023)
Resistance Nodulation Division (RND) efflux systems are ubiquitous transporters in Gram-negative bacteria that provide protection against antimicrobial agents and thereby enhance survival in virtually all environments these prokaryotes inhabit. Vibrio cholerae is a dual lifestyle enteric pathogen that spends much of its existence in aquatic environments. An unwitting encounter with a human host can lead to V. cholerae intestinal colonization by strains that encode cholera toxin and toxin co-regulated pilus virulence factors leading to potentially fatal cholera diarrhea and dissemination in the environment. Adaptive response mechanisms to host factors encountered by these pathogens are therefore critical both to engage survival mechanisms such as RND-mediated transporters and to induce timely expression of virulence factors. Sensing of cues encountered in the host may therefore activate more than protective responses such as efflux systems, but also be coordinated to initiate expression of virulence factors. This review summarizes recent advances that contribute towards the understanding of RND efflux physiological functions and how the transport systems interface with the regulation of virulence factor production in V. cholerae.